Gut microbiome and metabolites: The potential key roles in pulmonary fibrosis - Wu, Yinlan; Li, Yanhong; Luo, Yubin; Zhou, Yu; Wen, Ji; Chen, Lu; Liang, Xiuping; Wu, Tong; Tan, Chunyu; Liu, Yi (Frontiers in Microbiology, 2022)
There are a wide variety of microbiomes in the human body, most of which exist in the gastrointestinal tract. Microbiomes and metabolites interact with the host to influence health. Rapid progress has been made in the study of its relationship with abenteric organs, especially lung diseases, and the concept the of "gut-lung axis" has emerged. In recent years, with the in-depth study of the "gut-lung axis", it has been found that changes of the gut microbiome and metabolites are related to fibrotic interstitial lung disease. Understanding their effects on pulmonary fibrosis is expected to provide new possibilities for the prevention, diagnosis and even treatment of pulmonary fibrosis. In this review, we focused on fibrotic interstitial lung disease, summarized the changes the gut microbiome and several metabolites of the gut microbiome in different types of pulmonary fibrosis, and discussed their contributions to the occurrence and development of pulmonary fibrosis.